2018
DOI: 10.1007/s10508-018-1282-8
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Correlates of Sexual Arrangements in a National Cohort of HIV-Negative Gay and Bisexual Men in the United States

Abstract: Sexual agreements have received considerable attention as an aspect of dyadic functioning associated with HIV risk. To date, this research has primarily utilized convenience samples which over-represented men from large urban areas and with higher HIV risk. The current study utilized a national cohort of 1,061 HIV-negative gay and bisexual men recruited to be geographically diverse within the U.S. The sample included 531 (50.0%) men who identified as single. Of the 530 partnered men, 240 (45.3%) were monogamou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 59 publications
(124 reference statements)
0
9
0
Order By: Relevance
“…In a handful of cross-sectional studies, adult lesbians in a committed relationship reported fewer depressive symptoms (Ayala & Coleman, 2000; Kornblith et al, 2016; Oetjen & Rothblum, 2000) and better psychological well-being (Wayment & Peplau, 1995) than those who were single. Among sexual minority men, romantic involvement has been linked with lower depressive symptoms and less use of some illicit drugs (Parsons et al, 2013; Starks et al, 2019). However, romantically involved sexual minority men did not use less marijuana or alcohol than single men (Starks et al, 2019).…”
Section: Relationship Involvement and Mental Health Among Sexual And mentioning
confidence: 99%
See 1 more Smart Citation
“…In a handful of cross-sectional studies, adult lesbians in a committed relationship reported fewer depressive symptoms (Ayala & Coleman, 2000; Kornblith et al, 2016; Oetjen & Rothblum, 2000) and better psychological well-being (Wayment & Peplau, 1995) than those who were single. Among sexual minority men, romantic involvement has been linked with lower depressive symptoms and less use of some illicit drugs (Parsons et al, 2013; Starks et al, 2019). However, romantically involved sexual minority men did not use less marijuana or alcohol than single men (Starks et al, 2019).…”
Section: Relationship Involvement and Mental Health Among Sexual And mentioning
confidence: 99%
“…Among sexual minority men, romantic involvement has been linked with lower depressive symptoms and less use of some illicit drugs (Parsons et al, 2013; Starks et al, 2019). However, romantically involved sexual minority men did not use less marijuana or alcohol than single men (Starks et al, 2019). Further, another study found that romantic involvement was not associated with rates of anxiety or depressive disorders among gay and lesbian adults and was associated with higher odds of anxiety disorders among bisexual adults (Feinstein et al, 2016).…”
Section: Relationship Involvement and Mental Health Among Sexual And mentioning
confidence: 99%
“…Estimated rates were as high as 79% among younger SMM (aged [18][19][20][21][22][23][24][25][26][27][28][29] [6]. More recent research has indicated that the likelihood of having condomless anal sex (CAS) with casual partners is comparable for single SMM and partnered SMM in non-monogamous sexual agreements [7,8]. Moreover, some evidence suggests that SMM in monogamous relationships who break their agreement and engage in CAS with casual partners may actually do so more frequently than non-monogamous and single men [7].…”
Section: Introductionmentioning
confidence: 99%
“…Roughly a decade ago, epidemiological studies estimated that between 35 and 68% of new HIV infections among SMM were transmitted between main or primary (rather than casual or anonymous) partners [4,5]. Recent evidence suggests that SMM in non-monogamous relationships (where main partners have agreed that sex with outside partners is permissible under some circumstances) engage in CAS with casual partners at rates comparable to single SMM [6,7]. While partnered SMM who have monogamous sexual agreements (where sex with outside partners is not permitted) are less likely to engage in CAS with casual partners, there is some indication that those who do so actually engage in more frequent CAS than non-monogamous SMM [6].…”
Section: Introductionmentioning
confidence: 99%